Regional Planning and the Environmental Impact of Coastal Tourism: The Mission Racine for the Redevelopment of Languedoc-Roussillon’s Littoral - Giacomo Parrinello; Renaud Bécot (Humanities, 2019)
Research on the coast has highlighted the role of mass tourism as a driver of littoral urbanization. This article emphasizes the role of public policy by focusing on Languedoc-Roussillon in Mediterranean France. This littoral was the target of a state-driven development initiative known as Mission Racine, which aimed to promote the growth of what was seen as a backward area via the development of seaside tourism. For that purpose, the Mission promoted coordinated interventions including forest management, eradication of mosquitoes, construction of resorts, and transport infrastructure. This large-scale redevelopment significantly reshaped the littoral environment, severely impacted pre-existing forms of coastal activities and launched a new tourism industry. The legacy of the Mission, however, also included innovative land-use planning, which established protected areas and sought to contain urbanization. This case study illustrates the ambiguities of public policies for the coast, which can act alternatively as drivers of development or conservation and at times of both, and therein lies the importance of a contextual analysis of their role.